Hubungan Religius Spiritual Dengan Stres Pada Ibu Rumah Tangga Dengan Hipertensi - Nurul Khusnul Khotimah; Rasdiyanah (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2022)
Introduction: Housewives were a group susceptible to stress. Stress was one of the causes of hypertension. Housewives who experienced stress had different levels of religious spirituality. Spiritual religion was one of the factors that affected a person's stress level, so it had an impact on blood pressure. Methods: This research uses analytic correlation research with a cross-sectional approach. The research location is in South Sulawesi with a sample size of 246, namely housewives who have hypertension using non-probability sampling with accidental sampling. The efficacy instrument was taken from a questionnaire modified by Rasdiyanah, (2020), spiritual-religious coping instruments and stress instruments using PSS (Perceived Stress Scale), and bivariate analysis using spearmank rank. Result: Based on the results of statistical tests between variables using Spearman's rank, the results showed that there was a relationship between religious spirituality and stress in housewives with hypertension of 0.002 (P <0.05). Conclusion: Spiritual religion in housewives who had hypertension was one of the causes of stress in housewives who had hypertension